Annual Report 2011-12 Planning Commission Government of India - Planning Commission (Planning Commission, 2011)
The Planning Commission was constituted in March, 1950 by a Resolution of the Government of India, and it works under the overall guidance of the National Development Council. The Planning Commission consults the Central Ministries and the State Governments while formulating Five Year Plans and Annual Plans and also oversees their implementation. The Commission also functions as an advisory Planning body at the apex level.
Planning Commission Government of India
Planning Commission Government of India